PRELIMINARY STUDY IN FINDING BIOELASTOMER BASED ON VEGETABLE OIL: DIMER ACID PREPARATION - Mili Purbaya; Didin Suwardin (Jurnal Dinamika Penelitian Industri, 2016)
Dimer acid is the main material in the synthesis of bioelastomer. The preparation of dimer acid from vegetable oil such as crude palm oil and jatropha seed oil via Diels-Alder reaction were investigated. The dimer acid based vegetable oil was obtained by reacting vegetable oil with 12% by weight of  acrylic acid and 0.05 – 0.15% by weight of  iodine catalyst at temperature 191.25 – 247.5 oC for 1 – 2 hours. Dimer acids were analyzed using Fourier transform infrared spectroscopy, degree of acidity and acid value determination. The results show that the degree acidity (pH) of dimer acid from crude palm oil and jatropha seed oil were 2.18 – 2.35 and 2.46 – 2.56, respectively. The acid value of dimer acid from palm oil is 89.07 – 90.07 mg KOH/g sample and acid value of dimer acid from the jatropha seed oil is 63.80 – 80.43 mg KOH/g sample. Although the acid value is still lower than the commercial dimer acid (Empol 1016), the FTIR results showed that both dimer acids had some dicarboxylic acid functional groups as appeared in Empol 1016. So both vegetable oils have potential as a raw material for bioelastomer synthesis.